Green supply chain practices, environmental management accounting and performance of ISO 14001 certified organizations - Mohd Jama, Noriza; Wui Kiet, Wong; Mohamed Saat, Maisarah; Othman, Aniza; Ramakrishnan, Suresh (International Journal of Engineering and Technology, 2018)
Globalization and growth of sustainability development have forced organisations to act comprehensively and sensitively towards environmental issues. In recent years, studies on Green Supply Chain Practices (GSCPs) and Environmental Management Accouting (EMA) have shown significant impact on Environmental Performance (ENP) and Economic Performance (ECP). Nevertheless, to date, no single framework is established to examine the implementation of GSCPs and EMA on ISO certified organisations. Specifically, how GSCPs are influencing the improvement in ENP and ECP and how the EMA information is used by ISO 14001 certified manufacturing organisations to induce cost saving benefits from the effect of positive environmental actions are yet to be determined. Thus, this study is inspired with the aims to bridge these gaps, by proposing a quantitative method to empirically test the hypotheses. A survey questionnaire is employed for the main data collection, targeted to examine the relationships within the constructs. A sample population is drawn from Malaysian ISO 14001 certified manufacturing organisations.  The targeted respondents are the Environmental Management Representatives (EMR) who are responsible for maintaining and updating organisational environmental initiatives.  This study uses the Structural Equation Modelling (SEM) to analyse the relationship encapsulated among GSCPs, EMA, ENP and ECP.  This study is expected to provide a set of useful references generated for operational managers, supply chain managers, accountants, EMRs and practitioners to pursuit for an integration of EMA into existing EMS and GSCPs adoption.  This is to enable the facilitation for organisations to achieve environmental sustainable development.